A Feasibility Study on the Establishment Wrapsa (Wrapped Pica Pica) in Nova Square, Brgy San Bartolome Novaliches Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
A meal a day is important because here, we can obtain our energy that we will be needed for a day. The researchers think a business that can help them solve this issue by providing a food establishment that can make a food in a more convenient way of preparing. The researchers come in a concept that can prepare in a short period of time and can consume in a convenient way. The concept of an establishment that only serves wrapped food. A wrap is a form of sandwich made with a soft flatbread rolled around a filling. The usual flatbreads are wheat tortillas, lavash, or pita. The researchers used the method of random survey. Random survey is a way to sample in which everyone in the population has a chance of being chosen for the sample, and whoever's picked is chosen completely at random. The researchers randomly surveyed 50 respondents by giving them questionnaires to answer, together with a free sample of 3 chosen product of the “The House of Wrap” to criticize by the people passing by if the product has a high potential to market or not. The total estimated cost of our product pricing or our suggested retail price had a positive feedback based on the research survey, the high percentage of the respondent are willing to spend their money for our product. The majority of the people surveyed choose facebook application as the most effective way to conduct advertising of our product. The high percentage of the respondent can easily access our food store and they are willing to go to our establishment. The location and visibility is another major consideration in determining the future profitability of the business. The researchers conclude that the limited flavor of “lumpia” could affect the taste of the customers according to its satisfaction. The researchers found out that unfamiliar taste or product can affect the business itself. Finding the right and stable place for our establishment. For further expansion of the business.
Keywords: wrap, wheat tortillas, soft flat bread roll